Habitat simplification affects nuclear-follower foraging association among stream fishes - Teresa, Fabrício Barreto [UNESP]; Romero, Renato de Mei [UNESP]; Casatti, Lilian [UNESP]; Sabino, José (Sociedade Brasileira de Ictiologia, 2011)
A interação nuclear-seguidor é um tipo particular de associação alimentar interespecífica que envolve uma espécie nuclear, que revolve ou vasculha o substrato, e espécies seguidoras, que acessam os itens alimentares disponibilizados pela atividade do nuclear. Neste estudo investigamos o efeito da estrutura do habitat sobre essa interação em um riacho no Planalto da Bodoquena, Centro-Oeste do Brasil. Foram registradas 272 interações durante 24 sessões de observação subaquática em áreas estruturalmente inalteradas e alteradas. A espécie nuclear dominante diferiu entre as áreas. Prochilodus lineatus foi a espécie nuclear dominante das áreas alteradas, enquanto que Leporinus macrocephalus foi a espécie nuclear dominante nas áreas inalteradas. A riqueza de espécies seguidoras por interação não diferiu entre as áreas, entretanto a abundância de seguidores foi maior nas áreas inalteradas do que nas alteradas. Essas diferenças parecem ser consequência das modificações na composição da comunidade e no comportamento alimentar das espécies nucleares que são, por sua vez, decorrentes das diferenças na composição do substrato e disponibilidade de alimento entre as áreas estruturalmente distintas.

Nuclear-follower interaction is a particular kind of interspecific foraging association that includes a nuclear species, which dig in or inspect the bottom, and follower species, which access the food items made available by the nuclear. In this study we examined the effect of habitat structure on nuclear-follower relationship in a stream of Bodoquena Plateau, Central-West Brazil. Foraging associations were registered while snorkeling in 24 observation sessions, totaling six hours in unaltered and altered sites. Overall, 272 nuclear-follower associations were registered, having four species acting as nuclear and seven as followers. The dominant nuclear species were different in each site. Prochilodus lineatus was the main nuclear species in the altered site and Leporinus macrocephalus in the unaltered site. The richness of follower species was similar between sites, however, follower species abundance per interaction were significantly higher in the unaltered site than in the altered site. These differences seem to be a consequence of the alterations in assemblage composition and feeding behavior of the nuclear species that presumably are affected by different substrate composition and food availability between the structurally distinct areas.
Keywords: Bodoquena Plateau; Feeding behavior; Habitat heterogeneity; Interspecific interaction; Substrate